(untitled) (International Journal of Studies in Nursing, 2022)
Emergency nursing of upper gastrointestinal bleeding caused by esophagogastric vein rupture caused by eating rough food was reported. The key to nursing is the timely identification of upper gastrointestinal bleeding and emergency treatment after bleeding. Psychological care and health education after first aid, and prevention of related complications. The rescue was successful in this case.